A multicenter international randomized phase III study comparing cisplatin in combination with irinotecan or etoposide in previously untreated small-cell lung cancer patients with extensive disease - Zatloukal, Petr; Cardenal, F.; Szczesna, A.; Gorbunova, V.; Moiseyenko, V.; Zhang, X.; Cisar, L.; Soria, J. -C.; Domine, M.; Thomas, Michael (Annals of oncology, 2010)
Background - This study compared irinotecan plus cisplatin (IP) with etoposide plus cisplatin (EP) in small-cell lung cancer patients with extensive disease. - Patients and methods - Patients were randomly assigned to receive cisplatin 80 mg/m2 and either irinotecan 65 mg/m2, days 1 and 8 or etoposide 100 mg/m2, days 1-3, every 3 weeks. - Results - Baseline characteristics were balanced between patients receiving IP (N = 202) or EP (N = 203). Median overall survival was nonsignificantly superior for patients receiving IP versus EP, 10.2 versus 9.7 months [hazard ratio (HR) 0.81, 95% confidence interval (CI) 0.65-1.01, P = 0.06] and 1- and 2-year survival rates were 41.9% versus 38.9% and 16.3% versus 8.2%, respectively. Noninferiority of IP versus EP was established, upper bound of the 95% CI of HR 1.01 (prespecified margin IP/EP <1.25). Overall response (39.1% versus 46.6%) and time to tumor progression (5.4 versus 6.2 months) were not superior for IP. Grade 3/4 vomiting (10.9% versus 4.4%) and diarrhea (15.4% versus 0.5%) were more common in the IP versus EP arm; grade 3/4 neutropenia was more frequent in the EP (59.6%) versus IP arm (38.1%). - Conclusions - Our data demonstrate the noninferiority of IP versus EP for survival in primarily Western patients with SCLC-ED. A meta-analysis is required to finally assess the role of irinotecan in this setting.
Gesehen am 17.04.2024